Pengembangan Afeksi Siswa melalui Pembelajaran di SLTA - Herman Nirwana (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
Government decision for developing affective domain at school is a wise policy. It is done by integrating the teaching of affective domain in all teaching activities, and the teachers here should be the models for their students. Teaching evaluation is focused on the process of teaching and group work. Through this activity the students will be able to live together, respect their diversity, and love each other.